Family Experiences and Sexual Victimization Histories: a Comparative Analysis Between Youth Sexual and Nonsexual Offenders - Yoder, Jamie (International journal of offender therapy and comparative criminology, 2018)
Youth who commit sexual offenses often have sexual victimization histories that occur in the family context. These victimization experiences can be exacerbated by other risks present in the family environment. This research study uses MANOVAs to explore how family environments including substance use, mental health, physical and emotional victimization experiences, attachment, and parenting styles differentiate subgroups of youth offenders including youth sexual offenders with (n = 179) and without (n = 176) sexual victimization histories, and nonsexual offenders without sexual victimization histories (n = 150). Results reveal that youth sexual offenders with sexual victimization histories had greater risks in family environments relative to youth sexual and nonsexual offenders without sexual victimization histories. Treatment and research implications are discussed.